2016
DOI: 10.1002/hyp.10929
|View full text |Cite
|
Sign up to set email alerts
|

Soil water content in southern England derived from a cosmic‐ray soil moisture observing system – COSMOS‐UK

Abstract: Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner.This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Comparison of these soil w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
111
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 30 publications
0
111
0
Order By: Relevance
“…Cosmos sensors provide direct field scale measurement of soil moisture to within a c. 150 m radius of the sensor [103]. Recently, Evans et al [104], who described a UK network of ground-based cosmos sensors, showed a reasonable correlation on two different sites (R 2 = 0.46, n = 837 days and R 2 = 0.59, n = 0.59) between soil moisture retrieved from ASCAT (grid 12.5 km 2 ) and the novel ground sensors. These results were achieved despite a mismatch in the spatial resolutions of the ASCAT and cosmos stations.…”
Section: Eo and Field Irrigationmentioning
confidence: 99%
“…Cosmos sensors provide direct field scale measurement of soil moisture to within a c. 150 m radius of the sensor [103]. Recently, Evans et al [104], who described a UK network of ground-based cosmos sensors, showed a reasonable correlation on two different sites (R 2 = 0.46, n = 837 days and R 2 = 0.59, n = 0.59) between soil moisture retrieved from ASCAT (grid 12.5 km 2 ) and the novel ground sensors. These results were achieved despite a mismatch in the spatial resolutions of the ASCAT and cosmos stations.…”
Section: Eo and Field Irrigationmentioning
confidence: 99%
“…Crops are mostly rain fed during the monsoon season and about 15%-20% are irrigated using groundwater, especially during winter. The CNRP data handling procedures for COSMOS-India are based on Evans et al [63]. Other hydrological monitoring in the area includes soil moisture monitoring (Stevens HydraProbes), weather variables (OTT climate station) and groundwater levels in bore wells.…”
Section: Karnataka Indiamentioning
confidence: 99%
“…Moreover, they employed the triple collocation (TC) method [62], but focusing on the TC error only. Evans et al [63] introduced the COSMOS-UK network and compared to the Joint UK Land Environment Simulator (JULES) hydrological model. A comparison to ASCAT has been presented to show the applicability of such a network.…”
Section: Introductionmentioning
confidence: 99%
“…% soil moisture) (Kohli et al, 2015;Franz et al, 2012). Worldwide several CRNS networks exist, such as the North American COSMOS network , the German CRNS network installed in the context of the TERENO infrastructure measure (Zacharias et al, 2011), the Australian COSMoZ network (Hawdon et al, 2014) and the British COSMOS-UK (Evans et al, 2016).…”
Section: Introductionmentioning
confidence: 99%